Interaction of the National Police of Ukraine and civil society institutions: concept and legal framework (Bulletin of Kharkiv National University of Internal Affairs, 2023)
In a state governed by the rule of law, the public plays a central role not only as a recipient of public services, but also as a subject involved in the implementation of many functions of state institutions. This involves not only public control over the activities of public authorities, but also the performance of tasks aimed at shaping the security environment in the state, performing law enforcement functions, etc.The introduction of martial law on the territory of Ukraine and the existence of real threats to national security have led to dramatic changes in the usual order of public administration, in particular in the activities of the security and defence sector, law enforcement agencies, local self-government, etc. Some normative changes were aimed at improving the legal relations that arose in the course of civil society institutions’ activities. Under the new conditions, not only the forms of activity have changed, but also its directions have expanded. In today’s realities, civil society institutions play a significant role in the implementation of the law enforcement function of the state, which is not only about ensuring public order and safety. The above-mentioned issues raise the task of improving the effectiveness of cooperation between the National Police of Ukraine and civil society institutions.Based on the results of a multidisciplinary generalisation of the scholars’ achievements in the field of Administrative Law, it has been determined that in a broad sense, interaction between the National Police of Ukraine and civil society institutions should be understood as their joint coordinated activities regulated and carried out in accordance with the requirements of current legislation, which may take various forms and is embodied in a large number of measures whose overall purpose is to ensure the formation of a secure environment in the State. It is emphasised that it is important to establish effective interaction between the above-mentioned entities to comply with the legal framework, to understand and apply it correctly in practice (to ensure its observance in practical activities), since this will guarantee its effectiveness and legitimacy.The legal principles of interaction between the National Police of Ukraine and civil society institutions include legality, publicity, openness, transparency and partnership. Given the realities of today, these provisions require further research, taking into account the changes undergone by the legal system of Ukraine.